Brasileirinhos: análise da representação midiática de jogadores de futebol - Galarreta, Jorge Francisco Puente Arnao (2015)
This work is about how the media build the identity of football players. We observed how the TV show Esporte Espetacular in the series videos Brasileirinhos depicts elements of the Brazilian national identity. The main goal is to analyze how this identity is present in the representation of football players in the series Brasileirinhos. The specific goals of this research are: i) to analyze how the TV media, mainly the show Esporte Espetacular, broadcasted in TV Globo, represents the Brazilian football players in the series Brasileirinhos; ii) to recognize the national identity elements depicted by the program; and iii) to identify the existing works on this topic. The theoretical contribution comes from the concepts on identity explained by authors as Hall (1999) and Castells (2000), Woodward (1999) and Anderson (1989), and the Brazilian authors DaMatta (1994), Holanda (1978) and Freyre (2001). Approaches on media representations on sports are also presented in this work. They have been systematized in four categories: the Myth, the Hero, the Idol, and the Celebrity, mainly according to Helal (2003) and Giglio (2007). The text analysis methodology of Casetti and Chio (1999) was applied for corpus analysis of the two videos selected. As a conclusion of this research, we realize that some national identity elements that were built along the time continue to be reinforced by the media. We can also relate the way the itinerary is followed with the representational condition of Myth for Dedé and Idol, Hero and Celebrity for Neymar. Likewise, we can also confirm that some relations and behaviors of the Brazilian society, addressed by the authors, still exist and can be seen in the video, as the sponsorship. Other relations are built by the program, as the patriarchal system and the football-art relation.